Effectiveness of a Cognitive Behavioral Therapy for Dysfunctional Eating among Patients Admitted for Bariatric Surgery: A Randomized Controlled Trial - Hege Gade; Jøran Hjelmesæth; Jan H. Rosenvinge; Oddgeir Friborg (Journal of Obesity)
Objective. To examine whether cognitive behavioral therapy (CBT) alleviates dysfunctional eating (DE) patterns and symptoms of anxiety and depression in morbidly obese patients planned for bariatric surgery. Design and Methods. A total of 98 (68 females) patients with a mean (SD) age of 43 (10) years and BMI 43.5 (4.9) kg/m2 were randomly assigned to a CBT-group or a control group receiving usual care (i.e., nutritional support and education). The CBT-group received ten weekly intervention sessions. DE, anxiety, and depression were assessed by the TFEQ R-21 and HADS, respectively. Results. Compared with controls, the CBT-patients showed significantly less DE, affective symptoms, and a larger weight loss at follow-up. The effect sizes were large (DE-cognitive restraint, g=-.92, P≤.001; DE-uncontrolled eating, g=-.90, P≤.001), moderate (HADS-depression, g=-.73, P≤.001; DE-emotional eating, g=-.67, P≤.001; HADS-anxiety, g=-.62, P=.003), and low (BMI, g=-.24, P=.004). Conclusion. This study supports the use of CBT in helping patients preparing for bariatric surgery to reduce DE and to improve mental health. This clinical trial is registered with NCT01403558.